Mid Holocene hunters and herders of southern cordillera, Northwest Argentina - Castro, Silvina Celeste (2013)
This paper explores the characteristics of human occupation in the area near the Argentine-Chilean international boundary, in the Andes cordillera (northwest of San Juan province). Characteristics of human occupation of these high altitude environments and changes in subsistence strategies that occurred during the Middle Holocene are evaluated. The study is based on the analysis of the materials at the site located in a seasonally environment rich in resources. The paper contributes to knowledge of the function and the variability of socio-cultural systems of the past in Andean environments in the southern part of the Northwest Argentina region (NOA). The problem is approached from studies of the organization of lithic technology, and osteometric analysis recovered at the ARQ-18 site. These studies indicate changes in subsistence and technological strategies of human groups that occupied ARQ-18, incorporating herding activities in a chronological range between 5100 and 4300 BP.